Climate risk and commodity currencies - Felix Kapfhammer; Vegard Høghaug Larsen; Leif Anders Thorsrud (Norges Bank, 2020)
The positive relationship between real exchange rates and natural resource income is well understood and studied. However, climate change and the transition to a lower-carbon economy now challenges this relationship. We document this by proposing a novel news media-based measure of climate change transition risk and show that when such risk is high, major commodity currencies experience a persistent depreciation and the relationship between commodity price fluctuations and currencies tends to become weaker.
hdl:11250/2727312
Keywords: C11; C53; D83; D84; E13; E31; E37; 330; Exchange Rates; Climate; Risk; Commodities